Evaluation of the special tahfidz program using the context, input, process, product model - Abror, Muhammad Buya Al-Madany; Suud, Fitriah M. (Universitas Ahmad Dahlan, 2024)
The special Tahfidz program is an option for many students who want to strengthen their memorization of the Qur'an. As part of the program, this activity involves an evaluation process. MBS encounters evaluation challenges, prompting this research to delve deeper into these issues and identify strategies to surmount them. This study aims to evaluate the special tahfidz program at PPM MBS Yogyakarta. This evaluation uses ex post facto with a mixed method evaluative approach and uses the CIPP evaluation model. The subjects of this research are in the form of the person in charge of the special tahfidz program, tutors and students who participate in the special tahfidz program. Data collection is carried out by means of interviews, observations and documentation. The results of the evaluation showed that 51% of students achieved the target that had been determined, 18% exceeded the memorization target and 31% of students had not reached the target. However, most of the indicators have been fulfilled so that it gets the title of